The current treatment of hip arthroplasty revision: a systematic review of the literature - Giaretta, Stefano; Lunardelli, Enrico; Di Benedetto, Paolo; Aprato, Alessandro; Spolettini, Pietro; Mancuso, Francesco; Momoli, Alberto; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Acetabular revision surgery is the most challenging aspect in hip prosthetic. There is lack of consensus on the optimal method of reconstructing the acetabular defects. The aim of this systematic review is to take stock of the state of the art on the options available and highlight which type of construct is the most reliable in usual clinical practice.Material and methods: The reporting of this systematic review was guided by the standards of the Preferred Reporting Items for Systematic Review and Meta-Analysis 2020 Statement.Electronic search of MEDLINE was performed from 1991 up to April 2021 to identify relevant studies for this review. Discussion: various surgical techniques have been adopted and proposed to treat acetabular bone defects: cemented cups, large-sized non-cemented acetabular cups, higher positioned cups, reinforcement rings, cage, oblong cups, custom triflange implants, high porous metal cups and augments. Bone defect defines the type of components to be implanted and among those, outcomes are various depending on the study taken into account, the component used and the degree of initial bone defect.Conclusions: In acetabular revision surgerythe use of TM cups and augment is a valid option in presence of major bone loss and pelvic discontinuities. In clinical practice the use of TM components replaced rings, while the cup-cage implant replaced conventional cages. TM augments and cups can be considered as the most promising technique in the reconstruction of wide acetabular defects, while the use of cages can be considered as a valid option in the elderly population.